Substantiation of the criteria for evaluating of the quality of restoring distorted images for the iterative algorithm in correlation detection systems - A. Yu. Liplianin; A. V. Khizhniak; A. V. Sergeenko; N. V. Tsarenkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The analysis of quality criteria for evaluating images susceptible subjected to distortions such as «blur» and «defocusing» has been carried out. The criterion for assessing the quality of the recovery process, defined as the degree of similarity of the histogram of the gradients of the reconstructed image with the distribution of brightness gradients obtained a priori, was substantiated.